Descripción de la calidad molinera del cultivo de arroz (Oryza sativa L. ssp. japónico). - Monar Coello, Ángel Sebastián (2022)
The present research work is about "Description of the milling quality of rice cultivation (Oryza sativa L. ssp. Japónico)". The data from which samples were analyzed at the Technical University of Babahoyo, Babahoyo city, Los Rios province, Ecuador. Of which it was raised as objective: To study the description of the milling quality of the rice crop (Oryza sativa L. ssp. japónico), the data taken from the milling quality project carried out by the Technical University of Babahoyo, of the which the entire process by which the rice is subjected was studied so that it served to know the process of husking, polishing, obtaining the powder and the rice. The variables that were studied were: percentage of impurity, percentage of humidity, grain density, weight of shell, weight of brown rice, weight of white mass, weight of powder, weight of broken grains-rice, and weight of polished grain. In this study it was determined that Japanese rice has good milling characteristics that cannot be compared with the varieties grown in Ecuador. It is recommended to carry out more studies on the milling quality of Japanese rice planted in different parts of the country, in order to determine where the crop is best adapted, in order to carry out the respective milling quality analysis, in which the management will be reflected of the crop